Posttraumatic Stress Related to Orlando Nightclub Shooting: LGBTQ Identity and Media Use. - First, Jennifer M.; Shin, Haejung; Figueroa-Caballero, Andrea; Okker-Edging, Katherine; Spialek, Matthew L.; Houston, J. Brian (Journal of Loss & Trauma, 2023)
This study examined posttraumatic stress symptoms in a sample of U.S. adults (N = 1015) to examine the mental health impact of the Pulse Nightclub shooting media exposure. Direct and indirect relationships between LGBTQ identify, media use, emotions to media, and posttraumatic stress symptoms (PTS) related to the Pulse Nightclub shooting were examined using Structural Equation Modeling (SEM). Results found Pulse shooting media use had a direct effect with emotional reactions and PTS, and identifying as LGBTQ had a direct effect between stronger emotional reactions and PTS. Results also found that discontinuing use of Pulse shooting media coverage mediated the relationship between exposure to media coverage and PTS.